2008
DOI: 10.1590/s0100-204x2008000700012
|View full text |Cite
|
Sign up to set email alerts
|

Atividade enzimática e perfil da comunidade bacteriana em solo submetido à solarização e biofumigação

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito da solarização e da biofumigação sobre a comunidade microbiana do solo, por meio da atividade da enzima beta-glicosidase e do perfil do 16S rDNA, determinado com PCR-DGGE. A solarização do solo, com cobertura de plástico, foi feita por períodos de dois, quatro e seis meses, e a biofumigação foi realizada pela incorporação de 2 e 5% (v/v) de cama-de-frango ao solo. Logo após a retirada da cobertura de plástico e aos 30 dias após a remoção, a atividade da be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
1
0
5
Order By: Relevance
“…The organic residues from grasses and intercroppings with legumes are of higher quality, that is, have a smaller C:N ratio, as the insertion of different plant families promotes the diversifying of plant root systems, which, consequently, improves the diversity of the deposited residue. Thereby, the β-glucosidase activity is altered, due to the direct relation that the enzyme has with the hydrolysis of easy to decompose organic compounds, and is highly related to C sources (Passos et al 2008). Stieven et al (2014) studied ICLS in the same region (Mato Grosso, Brazil) and observed that this enzyme Plant diversity in integrated crop-livestock systems increases the soil enzymatic activity in the short term activity is directly related to, mainly, the quality of the organic residue added to the soil.…”
Section: Resultsmentioning
confidence: 99%
“…The organic residues from grasses and intercroppings with legumes are of higher quality, that is, have a smaller C:N ratio, as the insertion of different plant families promotes the diversifying of plant root systems, which, consequently, improves the diversity of the deposited residue. Thereby, the β-glucosidase activity is altered, due to the direct relation that the enzyme has with the hydrolysis of easy to decompose organic compounds, and is highly related to C sources (Passos et al 2008). Stieven et al (2014) studied ICLS in the same region (Mato Grosso, Brazil) and observed that this enzyme Plant diversity in integrated crop-livestock systems increases the soil enzymatic activity in the short term activity is directly related to, mainly, the quality of the organic residue added to the soil.…”
Section: Resultsmentioning
confidence: 99%
“…As enzimas microbianas têm participação essencial nos processos relacionados à qualidade do solo, uma vez que é por meio delas que os microorganismos do solo degradam moléculas orgânicas complexas em simples que podem ser assimiladas. Além de permitir que os micro-organismos tenham acesso à energia e nutrientes presentes em substratos complexos, as enzimas extracelulares são responsáveis pela decomposição e mineralização de nutrientes no solo, disponibilizando-os também para as plantas e promovendo a ciclagem de nutrientes no solo (MAKOL e NDAKIDEMI, 2008;CENCIANI et al, 2008;PASSOS et al, 2008;SAID e PIETRO, 2004).…”
unclassified
“…Médias seguidas por letras iguais, nas colunas, não diferem pelo teste de Duncan (5%). Fonte: Adaptado de Passos et al (2008).…”
Section: Desenvolvimentounclassified